Impact of Information and Communications Technology Parameters on Performance of Nepalese Commercial Banks - Bhatt, Sapana; Pradhan, Sumit (Nepalese Journal of Business, 2024)
This study examines the impact of information and communications technology parameters on the performance of Nepalese commercial banks. Bank performance is selected as the dependent variable. The selected independent variables are mobile banking, internet banking, POS banking, QR code banking, SMS alert system, ATM banking and internet security features. The primary source of data is used to assess the opinions of the respondents regarding information and communications technology parameters, its usage, and its impact on the performance of Nepalese commercial banks. The study is based on primary data with 120 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of information and communications technology parameters on the performance of Nepalese commercial banks. The study showed that internet security features have positive impact on the performance of banks. It indicates that stronger internet security leads to increase in performance of banks. Similarly, mobile banking has a positive impact on the performance of the banks. It indicates that increase in the usage and availability of mobile banking services leads to increase in the level of bank performance. Moreover, POS banking has a positive relationship with the performance of the banks. It indicates that the utilization of POS banking services leads to increase in the level of bank performance. Furthermore, internet banking has a positive impact on performance of banks. It indicates that increase in the usage and adoption of internet banking services leads to increase in the level of bank performance. Likewise, QR code banking (QR) has a positive impact on the performance of the banks. It indicates that the better implementation of QR code banking services leads to increase in the level of bank performance. Similarly, SMS alert system has a positive impact on the performance of the banks. It indicates that the better implementation of SMS alert systems leads to increase in the level of bank performance. Further, ATM service has a positive impact on the performance of the banks. It indicates that increase in the usage and availability of ATM services leads to increase in the level of bank performance.